Findings from the Yearbook 2010 Section on Decision Support Systems - Ruch, P.; Section Editor for the IMIA Yearbook Section on Decision Support Systems (Yearbook of Medical Informatics, 2010)
Objective: To summarize current excellent research in the field of computer-based decision support systems in health and healthcare.Methods: We provide a synopsis of the articles selected for the IMIA Yearbook 2010, from which we attempt to derive a synthetic overview of the activity and new trends in the field.Results: While the state of the research in the field of medical decision support systems is illustrated by a set of fairly heterogeneous studies, it is possible to identify trends. Thus, clearly, the importance of studies related to computerized prescription order entry (CPOE) systems and guidelines management systems for both medical decision making and care providers, occupies a central role in the field, with application affecting also EHR vendors. In parallel, we observe translational interests for developing bridges with results generated by molecular biology, where the mass of data generated by high/ throughput experiments and large-scale genome analysis projects, raises specific processing challenges.Conclusions: The best paper selection of articles on decision support shows examples of excellent research on methods concerning original development as well as quality assurance of previously reported studies. This selected set of scientific investigations demonstrates the needs for computerized applications to transform the biomedical data overflow into more operational clinical knowledge. Altogether these papers support the idea that more elaborated computer tools, likely to combine heterogeneous contextual contents, are needed.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; decision support systems